Illustrated State‐of‐the‐Art Capsules of the ISTH 2019 Congress in Melbourne, Australia. Issue 3 (5th July 2019) - Ward, Christopher M.; Andrews, Robert K.; ,
Abstract: The 27th Congress of the International Society of Thrombosis and Haemostasis (ISTH) is an international conference held July 6‐10, 2019, in Melbourne, the capital of the state of Victoria, Australia. The ISTH congress has previously been held every other year, with the Scientific and Standardization Committee (SSC) meeting held annually, until 2019 when it became one combined annual meeting of the ISTH and SSC. The conference covers clinical and basic aspects of hemostasis and thrombosis, and this year includes 5 Plenary lectures and >50 State of Art (SOA) lectures, presented by internationally recognized speakers, as well as numerous oral session and poster presentations selected from submitted abstracts, including many early career and reach the world support recipients. This SOA review article in RPTH contains concise Illustrated Review Articles or 'Capsules' consisting of short text, three references and a figure, with topics including stroke, cancer‐associated thrombosis, hemophilia, coagulation, the interface between infection and inflammation, and in the experimental and discovery areas, megakaryocyte biology and platelet production, structure‐function of key receptors and coagulation factors, and emerging new roles for thrombotic/hemostatic factors. Together, these articles highlight novel findings which will advance knowledge and with the potential to change clinical practice and improve outcomes. It is hoped that conference attendees and followers will enjoy utilizing the images for ongoing education and during the conference for live tweeting during sessions, to assist in the broadcasting and promotion of the science to those unable to attend, or who have chosen to attend a concurrent session. Use #IllustratedReview and #ISTH2019 on social media.